Anisometric engineering of particle interfaces: Multidimensional characterization and gram‐scale production - Klupp Taylor, Robin; Meincke, Thomas; Sadafi, Fabrizio-Zagros; Walter, Johannes; Pflug, Lukas; Watanabe, Shun; Peukert, Wolfgang; Stingl, Michael (Chemie Ingenieur Technik (Special Issue: ProcessNet‐Jahrestagung und 33. DECHEMA‐Jahrestagung der Biotechnologen 2018), 2018)
A simple continuous-flow liquid-phase approach for the partial coating of nanoscale particles with metal was established [1]. Unique to this is the surface conformal and morphology-tailored growth of the metal. Due to their anisotropic surface character, the resulting materials are potentially relevant as particulate surfactants or for the assembly of novel photonic, catalytic or theranostic materials. In this contribution, three significant challenges are described that have recently been tackled. Firstly, it is shown how the use of a KM type micromixer with very short characteristic mixing times facilitates the understanding of the metal coating growth process. Secondly, the application of multiwavelength analytical ultracentrifugation for the determination of yield, coating thickness, and coverage distribution of the metal patches is considered. The validity of the measurements through microscopy and spectroscopy is confirmed and it is demonstrated how this characterization method can be employed to support process design. Finally, it is illustrated how the continuous flow approach can be developed in order to produce anisotropic metal-coated particles on the gram scale, and a first analysis of the novel optical properties of the powders is provided. [1] T. Meincke, H. Bao, L. Pflug, M. Stingl, R. N. Klupp Taylor, Chem. Eng. J. 2016, 308, 89. DOI: https://doi.org/10.1016/j.cej.2016.09.0

On-Demand Coupling of Electrically Generated Excitons with Surface Plasmons via Voltage-Controlled Emission Zone Position - Zakharko, Yuriy; Held, Martin; Sadafi, Fabrizio-Zagros; Gannott, Florentina; Mandavi, Ali; Peschel, Ulf; Klupp Taylor, Robin; Zaumseil, Jana (ACS Photonics, 2016)
The ability to confine and manipulate light below the diffraction limit is a major goal of future multifunctional optoelectronic/plasmonic systems. Here, we demonstrate the design and realization of a tunable and localized electrical source of excitons coupled to surface plasmons based on a polymer light emitting field-effect transistor (LEFET). Gold nanorods that are integrated into the channel support localized surface plasmons and serve as nanoantennas for enhanced electroluminescence. By precise spatial control of the near-infrared emission zone in the LEFET via the applied voltages the near-field coupling between electrically generated excitons and the nanorods can be turned on or off as visualized by a change of electroluminescence intensity. Numerical calculations and spectroscopic measurements corroborate significant local electroluminescence enhancement due to the high local density of photonic states in the vicinity of the gold nanorods. Importantly, the integration of plasmonic nanostructures hardly influences the electrical performance of the LEFETs, thus, highlighting their mutual compatibility in novel active plasmonic devices.
Keywords: surface plasmon polariton; organic semiconductor; field-effect transistor; electroluminescence; Purcell effect; active plasmonics

On the complex role of ammonia in the electroless deposition of curved silver patches on silica nanospheres - Sadafi, Fabrizio-Zagros; Sauerbeck, Christian; Braunschweig, Björn; Klupp Taylor, Robin (Crystengcomm, 2018)

Patchy particles made easy: Developing general colloidal approaches to produce anisotropic building blocks for novel functional materials - Klupp Taylor, Robin; Bao, Huixin; Sadafi, Fabrizio-Zagros (Engineering Sciences and Fundamentals 2013 - Core Programming Area at the 2013 AIChE Annual Meeting: Global Challenges for Engineering a Sustainable Future, 2013)

Radial Growth in 2D Revisited: The Effect of Finite Density, Binding Affinity, Reaction Rates, and Diffusion - Bihr, Timo; Sadafi, Fabrizio-Zagros; Smith, Ana-Suncana; Klupp Taylor, Robin; Seifert, Udo (Advanced Materials Interfaces, 2017)
Dendrite growth of metal patches on colloidal particles shows a variety of structures depending on the preparation conditions. The morphology of these patches suggests a cross-over from a reaction to a diffusion limited growth, implicating diffusion on the particle surface. Interestingly, the morphological and optical characteristics of the patches continuously change between two limiting behaviors. To understand this growth process, extensive simulations are performed, studying the fractal dimension and the dynamics of growth of a patch on a particle of a finite size, as a function of the initial density and the binding affinity of diffusing tracers. Several important growth regimes are characterized that enable to optimize the pathway for the synthesis of optically active, patchy particles.
Keywords: LIMITED AGGREGATION; CELL-ADHESION; FRACTAL AGGREGATION; COLLOIDAL SYNTHESIS; NANOSPHERES; DIMENSIONS; SIMULATION; NUCLEATION; PARTICLES; STABILITY